Postmortem diagnosis of diabetes mellitus and its complications - Palmiere, Cristian (Croat Med J, 2015)
Diabetes mellitus has become a major cause of death worldwide and diabetic ketoacidosis is the most common cause of death in children and adolescents with type 1 diabetes. Acute complications of diabetes mellitus as causes of death may be difficult to diagnose due to missing characteristic macroscopic and microscopic findings. Biochemical analyses, including vitreous glucose, blood (or alternative specimen) beta-hydroxybutyrate, and blood glycated hemoglobin determination, may complement postmortem investigations and provide useful information for determining the cause of death even in corpses with advanced decompositional changes. In this article, we performed a review of the literature pertaining to the diagnostic performance of classical and novel biochemical parameters that may be used in the forensic casework to identify disorders in glucose metabolism. We also present a review focusing on the usefulness of traditional and alternative specimens that can be sampled and subsequently analyzed to diagnose acute complications of diabetes mellitus as causes of death.